2022
DOI: 10.1021/acs.jctc.1c01222
|View full text |Cite
|
Sign up to set email alerts
|

Toward Convergence in Folding Simulations of RNA Tetraloops: Comparison of Enhanced Sampling Techniques and Effects of Force Field Modifications

Abstract: Atomistic molecular dynamics simulations represent an established technique for investigation of RNA structural dynamics. Despite continuous development, contemporary RNA simulations still suffer from suboptimal accuracy of empirical potentials (force fields, ffs) and sampling limitations. Development of efficient enhanced sampling techniques is important for two reasons. First, they allow us to overcome the sampling limitations, and second, they can be used to quantify ff imbalances provided they reach a suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(71 citation statements)
references
References 112 publications
7
63
0
Order By: Relevance
“… 8 In a separate manuscript, we showed that using ST-MetaD with MetaD on eRMSD greatly improved the performance of pure ST for RNA tetraloops. 51 Similar conclusions were drawn in ref ( 54 ), where parallel tempering-MetaD 55 , 56 with MetaD on the number of native contacts, 57 a variable highly correlated with eRMSD, was suggested to be significantly more efficient than pure parallel tempering for a GNRA tetraloop. ST-MetaD simulations were carried out using a GPU-capable version of GROMACS2018 44 in combination with PLUMED 2.5 58 , 59 (see section 2.7 for more details about implementation of the gHBfix function within PLUMED code and Table 1 in the Supporting Information for a full list of standard as well as enhanced sampling simulations).…”
Section: Methodssupporting
confidence: 80%
“… 8 In a separate manuscript, we showed that using ST-MetaD with MetaD on eRMSD greatly improved the performance of pure ST for RNA tetraloops. 51 Similar conclusions were drawn in ref ( 54 ), where parallel tempering-MetaD 55 , 56 with MetaD on the number of native contacts, 57 a variable highly correlated with eRMSD, was suggested to be significantly more efficient than pure parallel tempering for a GNRA tetraloop. ST-MetaD simulations were carried out using a GPU-capable version of GROMACS2018 44 in combination with PLUMED 2.5 58 , 59 (see section 2.7 for more details about implementation of the gHBfix function within PLUMED code and Table 1 in the Supporting Information for a full list of standard as well as enhanced sampling simulations).…”
Section: Methodssupporting
confidence: 80%
“…Recently, several of these contacts were monitored in MD simulations including a labile 0BPh contact involving the G of the first stem base pair [ 54 , 59 ]. Such C-H…O contact [ 88 ] are very subtle and difficult to model although recent parameterization efforts involving a modification of vdW radii improved the sampling of the loops.…”
Section: Discussionmentioning
confidence: 99%
“…Such C-H…O contact [ 88 ] are very subtle and difficult to model although recent parameterization efforts involving a modification of vdW radii improved the sampling of the loops. Unfortunately, the conclusions of these studies reveal that we are currently far from mastering all interactions that are essential for modeling the apparently “simple” tetraloop systems [ 54 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations